2021
DOI: 10.3390/antiox10060889
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sugar Type Addition and Fermentation Temperature on Pomegranate Alcoholic Beverage Production and Characteristics

Abstract: The present study focuses on the production of pomegranate alcoholic beverage (PAB) from juice of the Wonderful variety. The effect of fermentation temperature (15 and 25 °C) and type of sugar added (adjustment to 20 °Brix) on the physicochemical characteristics, bioactive compounds, and volatile composition were studied. Sucrose, concentrated pomegranate juice, concentrated grape juice, and honey were used to increase the initial sugar content. The produced PABs contained ethanol in concentrations ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“… Cai et al (2019) revealed that throughout the liquor brewing process, more ethyl acetate was produced during fermentation and became a crucial volatile component. Ethyl acetate was also identified as one of the most abundant esters in pomegranate alcoholic beverages, which was detected in all fermented samples ( Kokkinomagoulos et al, 2020 , 2021 ). In the present study, two esters (ethyl acetate and butyl acetate) were identified, which exhibited a slight increase after fermentation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“… Cai et al (2019) revealed that throughout the liquor brewing process, more ethyl acetate was produced during fermentation and became a crucial volatile component. Ethyl acetate was also identified as one of the most abundant esters in pomegranate alcoholic beverages, which was detected in all fermented samples ( Kokkinomagoulos et al, 2020 , 2021 ). In the present study, two esters (ethyl acetate and butyl acetate) were identified, which exhibited a slight increase after fermentation.…”
Section: Resultsmentioning
confidence: 96%
“…They further explored the effects of fermentation temperature and the type of sugar added to the pomegranate alcoholic beverage. The major volatile compounds in the pomegranate alcoholic beverage, such as 3-methyl-1-butanol and 2-methyl-1-butanol, were detected by GC–MS ( Kokkinomagoulos et al, 2021 ). Bontsidis et al (2021) fermented chokeberry juice by Lactobacillus paracasei and analyzed the change in volatile compounds using GC–MS.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of alcohol fermentation, the alcohol content was 9.60 vol.%. The addition of sucrose is an important way to increase the ABV of C. paliurus –kiwi wine [ 33 ]. During the resting process, the concentration of alcohol content remained the same.…”
Section: Resultsmentioning
confidence: 99%